URGENSI ILMU ‘ILAL AL-HADĪTH - Rahmin Talib Husain (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2017)
‘Ilal al-hadīth study is a kind of study that investigates hadith and has strategic values in other hadith studies. This article investigates descriptively that aims at exploring and positioning ‘ilal al-hadīth study for developin hadith study in the future since there is minimum appreciation for hadith scholars in general toward the existence and the development of this study. Key words: Hadith, ‘ilal al-hadīth, ṣahih, sanad, matan